2016
DOI: 10.1016/j.radmeas.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dosimeter properties of MgO transparent ceramic doped with C

Abstract: We have investigated the photoluminescence (PL), scintillation and thermally-stimulated luminescence (TSL) dosimeter properties of MgO ceramic doped with C ions (0.001, 0.01 and 0.1 %). The samples were synthesized by a Spark Plasma Sintering (SPS) technique. The PL emission peaks appeared around 400 and 750 nm in all the samples. The PL decay time constants at 400 nm were ~10 and ~100 ns which were on the typical order of F + center in the undoped MgO. The scintillation emission peaks were detected at 330, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…All samples exhibited two main emission peaks at 395 nm and 468 nm which were attributed to UV and visible emission respectively. 37 The UV emission was produced by the recombination between electrons and holes, while the visible emission was related to the defects such as oxygen vacancies and Mg interstitials. 38 Thus, the increased intensity of the PL bands in Fe-doped MgO NPs samples suggested that both the density and intensity of sample defects were enhanced together with oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…All samples exhibited two main emission peaks at 395 nm and 468 nm which were attributed to UV and visible emission respectively. 37 The UV emission was produced by the recombination between electrons and holes, while the visible emission was related to the defects such as oxygen vacancies and Mg interstitials. 38 Thus, the increased intensity of the PL bands in Fe-doped MgO NPs samples suggested that both the density and intensity of sample defects were enhanced together with oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] On the other hand, transparent ceramics were expected as a nextgeneration material form for some phosphors. [7][8][9] As general advantages of transparent ceramics, there are features as follows: (ⅰ) thermal and mechanical properties of transparent ceramics are superior to those of single crystals and glasses. (ⅱ) Ceramics can be synthesized at a lower temperature in comparison with single crystals.…”
Section: Introductionmentioning
confidence: 99%